Ethnic variations of values, emotional intelligence, and job performance: the case of a multinational subsidiary in a multi-ethnic context - Zawawi, Dahlia; Tsang, Denise; Mustaffa, Zaidah; Rodriguez, Adriana Maria Ortega (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2019)
This study examines the relationship between individual and cultural values, emotional intelligence (EI) and job performance across three major ethnic groups in a multinational subsidiary in Malaysia. Multinational subsidiaries in ethnically diverse host country such as Malaysia face increasing challenges of managing highperformance employees. Malaysia has hosted foreign direct investment since the 1970s and presents a unique context to explicate the limited attention of intra-national variations in international management research. The study presents a quantitative analysis of a sample of 156 managers in a multinational subsidiary, examining the association between cultural values, individual values, emotional intelligence and individual level job performance across three major ethnic groups – Malay, Chinese and Indian. Findings from this study have identified several variations in values held individually and the ones practised within a culture. Basically, the link between individual values, emotional intelligence, and job performance is highlighted while at the same time the indication of the idea that emotional intelligence is interconnected to the ethnic groups is provided.